2019
DOI: 10.3390/ijms20205034
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia/Reperfusion Injury Revisited: An Overview of the Latest Pharmacological Strategies

Abstract: Ischemia/reperfusion injury (IRI) permeates a variety of diseases and is a ubiquitous concern in every transplantation proceeding, from whole organs to modest grafts. Given its significance, efforts to evade the damaging effects of both ischemia and reperfusion are abundant in the literature and they consist of several strategies, such as applying pre-ischemic conditioning protocols, improving protection from preservation solutions, thus providing extended cold ischemia time and so on. In this review, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
201
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(209 citation statements)
references
References 388 publications
(555 reference statements)
2
201
1
5
Order By: Relevance
“…In this article, we revisited the role of saturated long-chain acylcarnitines in the control of both cellular Ca 2+ homeostasis and mitochondrial energy metabolism. Most recent reviews devoted to the studies of reperfusion/injury and cardioprotective mechanisms are focused on harmful effects of calcium and reactive oxygen species (ROS) [ 57 , 58 , 59 , 60 ]. The mechanisms of acute lipotoxicity are analyzed separately of Ca 2+ effects and include the inhibition of mitochondrial oxidative phosphorylation and the accumulation of ROS induced by long-chain fatty acids or respective acylcarnitines [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we revisited the role of saturated long-chain acylcarnitines in the control of both cellular Ca 2+ homeostasis and mitochondrial energy metabolism. Most recent reviews devoted to the studies of reperfusion/injury and cardioprotective mechanisms are focused on harmful effects of calcium and reactive oxygen species (ROS) [ 57 , 58 , 59 , 60 ]. The mechanisms of acute lipotoxicity are analyzed separately of Ca 2+ effects and include the inhibition of mitochondrial oxidative phosphorylation and the accumulation of ROS induced by long-chain fatty acids or respective acylcarnitines [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recent reviews devoted to the studies of reperfusion/injury and cardioprotective mechanisms are focused on harmful effects of calcium and reactive oxygen species (ROS) [ 57 , 58 , 59 , 60 ]. The mechanisms of acute lipotoxicity are analyzed separately of Ca 2+ effects and include the inhibition of mitochondrial oxidative phosphorylation and the accumulation of ROS induced by long-chain fatty acids or respective acylcarnitines [ 59 , 60 ]. It is well established that rapid influx and accumulation of Na + and Ca 2+ in cytoplasm, which generally occurs in I/R, may lead to the accumulation of [Ca 2+ ] i and [Ca 2+ ] m and mitochondrial (mPTP) or mitochondrial-independent cell death [ 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nayak et al reported cases of hand replantation involving 6–8 hours of warm ischemia and concluded that arterialization prior to replantation should be performed immediately, in order to delay tissue necrosis and enable limbs to survive after long warm ischemic time [ 10 ]. The replantation technique includes irrigation and debridement, identification, dissection, marking of nerves and blood vessels, bone shortening, internal fixation, extensor tendon grafting, flexor tendon grafting, arterial, vein and nerve grafting, and skin graft (to close the wound) [ 1 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ROS levels are controlled by intracellular antioxidants; when blood flow is returned to hypoxic tissues, oxygen molecules will bind to each other, which—given the absence of a supply of local antioxidants—will cause a surge in ROS. In the end, instead of promoting cell recovery, the excessive amount of ROS can cause cellular damage [ 11 ]. Moreover, prolonged ischemia triggers inflammation and influences the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of ischemia and reperfusion, there is a dependence between reperfusion injury and ischemia time, and the ischemia process itself can cause injury, which is also the basis of reperfusion injury [31,32] . The essence of reperfusion injury is to further aggravate or convert the injury in ischemic phase into irreversible injury after blood ow recovery [33] . So the rst thing that affects reperfusion injury is ischemia time [34] .…”
Section: Discussionmentioning
confidence: 99%